Difficulties In Understanding The Science Learning Material as Related to Educational Psychology: Kesulitan dalam Memahami Materi Pelajaran IPA yang Dikaitkan dengan Psikologi Pendidikan - Umami, Riza (Psikologia : Jurnal Psikologi, 2021)
This study aims to discuss the difficulties in understanding science subject matter associated with educational psychology. The research method used is descriptive qualitative method, namely the data obtained by the author is presented in the discussion. In obtaining data, the author uses literature in the form of books and journals. The results showed that there are various kinds of difficulties in understanding science subject matter and there are factors that can be linked to educational psychology and also how to overcome these difficulties.